The happiest place on Earth : the incredible story of Walt Disney's Disneyland - Hahn, Don; Merritt, Christopher (Disney Editions Deluxe, 2025)
Disneyland is the only park Walt walked through and tinkered with during the last 11 years of his life. For Disneyland's 70th anniversary, Disney fans will get an in-depth visual look at the planning and creation of those first 11 years of Walt Disney's original theme park. This treasure trove of Disney history will take fans through the pre-production and realization process Walt used during the earliest days of his nascent theme park.